2018
DOI: 10.1098/rsos.172162
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rates are significantly lower in abyssal Holothuroidea than in shallow-water Holothuroidea

Abstract: Recent analyses of metabolic rates in fishes, echinoderms, crustaceans and cephalopods have concluded that bathymetric declines in temperature- and mass-normalized metabolic rate do not result from resource-limitation (e.g. oxygen or food/chemical energy), decreasing temperature or increasing hydrostatic pressure. Instead, based on contrasting bathymetric patterns reported in the metabolic rates of visual and non-visual taxa, declining metabolic rate with depth is proposed to result from relaxation of selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Due to the intrinsic association between the metabolic rate and locomotory capacity, this implies that the relationship between metabolic rate and skew magnitude is negatively correlated in many crustaceans lineages. There are additional multiple lines of evidence that support our results: eurybathic organisms generally exhibit decreased metabolic rates (Brown et al, 2018;Seibel & Drazen, 2007), troglobitic isopods have a much lower metabolic rate than terrestrial isopods (Kleimenov & Alekseeva, 2002), and hypoxia negatively affects the metabolic rate in isopods (Stevens et al, 2010). Yet, we found that troglobitic and deep-sea (low oxygen environment) crustacean taxa exhibit elevated skew and ω magnitudes.…”
Section: The Unified Theory: Metabolic Rate Skew Magnitude and Dn/ds Rate Are Intrinsically Correlated Through The Selection For Locomotosupporting
confidence: 76%
“…Due to the intrinsic association between the metabolic rate and locomotory capacity, this implies that the relationship between metabolic rate and skew magnitude is negatively correlated in many crustaceans lineages. There are additional multiple lines of evidence that support our results: eurybathic organisms generally exhibit decreased metabolic rates (Brown et al, 2018;Seibel & Drazen, 2007), troglobitic isopods have a much lower metabolic rate than terrestrial isopods (Kleimenov & Alekseeva, 2002), and hypoxia negatively affects the metabolic rate in isopods (Stevens et al, 2010). Yet, we found that troglobitic and deep-sea (low oxygen environment) crustacean taxa exhibit elevated skew and ω magnitudes.…”
Section: The Unified Theory: Metabolic Rate Skew Magnitude and Dn/ds Rate Are Intrinsically Correlated Through The Selection For Locomotosupporting
confidence: 76%
“…Previous studies have suggested that mutation rates are sensitive to many factors, including environmental energy 14 , metabolic rate 15 , life-history traits 16 and, in particular, generation times 17 . Hadal species reportedly have comparatively low metabolic rates 18 , so the MHS may have a 'slow life'. Coincidentally, we observed that the female MHS produced fewer but larger eggs than females of other snailfish species, suggesting that they may have a specialized reproduction strategy (for example, epimeletic behaviour and/or eggs that hatch as juveniles rather than larvae), which could further increase the generation time.…”
mentioning
confidence: 99%
“…Direct in situ or ex situ respiration measurements on deep‐sea meiofauna have not yet been successfully done, as the animals do not survive the pressure difference when recovered to the surface, and no device has yet been built for in situ measurements. Recent in situ metabolic rates measured for the megafauna (Holothuroidea) revealed no differences between shallow‐water and bathyal individuals, but rates were considerably lower for abyssal organisms (Brown et al 2018). These results can give an indication of potentially lower metabolic rates for abyssal meio‐ and macrofauna, but currently these measurements are still lacking.…”
Section: Ecological Tracers: Stable Isotopes/functional Traits/biomassmentioning
confidence: 99%